2018
DOI: 10.1123/jmld.2017-0026
|View full text |Cite
|
Sign up to set email alerts
|

Children’s Throwing and Striking: A Longitudinal Study

Abstract: Object control skills (OCS) provide children the means to be physically active. However, gender equality in some OCS remains elusive. Particularly troublesome is the basic throwing pattern and, by extension, the striking pattern, both of which rely on forceful, rapid rotation of the pelvis, trunk, and shoulders. Some scholars argue that sex differences in throwing and striking are rooted in human evolution. The purpose of this study was to examine development of throwing and striking at the fundamental movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…These kinds of patterns are inherited through natural selection [ 67 ]. A previous study speculates that mature throwing is more likely an innate skill whose development is biologically determined and somewhat difficult to be influenced by nurture, and the same may be true of striking [ 68 ]. Sociological factors and behavior habits may also contribute to gender differences in proficiency in object control.…”
Section: Discussionmentioning
confidence: 99%
“…These kinds of patterns are inherited through natural selection [ 67 ]. A previous study speculates that mature throwing is more likely an innate skill whose development is biologically determined and somewhat difficult to be influenced by nurture, and the same may be true of striking [ 68 ]. Sociological factors and behavior habits may also contribute to gender differences in proficiency in object control.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with those of several studies [ 8 , 14 , 19 ]. One explanation may be that boys and girls practice different activities in leisure time, resulting in more object control for boys and balancing skills for girls [ 28 , 29 ]. However, this may not completely explain the difference in GMC proficiency, as, in our study, the rate of development did not differ between boys and girls.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that this difference in balancing and object control proficiency already appears before the third grade and persists across the grades. This may be a consequence of genetic predispositions [ 28 ]. However, further research is needed to gain more insight into the causes of the difference in different aspects of GMC between boys and girls over time.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 2041 articles found on Google Scholar from January 1 st 2014 to June 20 th 2019, we found that 758 used descriptors for ANOVA-based methods (viz., "repeated-measures", "mixed-factor", "mixed-factorial"), whereas only 15 used descriptors for mixed-effect regression models (viz., "mixed-effect", "multilevel model" or "MLM", "hierarchical linear model" or "HLM"). Of the 15 articles that employed mixed-effects regression only two were longitudinal designs (Cantin et al, 2014;Angell et al, 2018), while the remainder had other nested data structures (e.g., Dixon et al, 2019). Thus, we estimate about 35% of all articles in these journals used ANOVA-based methods for managing repeated observations, whereas less than 1% used mixed-effects regression-based methods.…”
mentioning
confidence: 96%